Oo meyo achimoowin St. Mark = The gospel according to St. Mark - Hunter, James, 1817-1882.; Bible Collection (Library of Congress) DLC (London : Printed for the British and Foreign Bible Society, 1855)
LC copy has Smithsonian Deposit bookplate; red Smithsonian Institution stamp on t.p. Inscription on front free endpaper recto: Smithsonian Institn. from Bernard R. Ross. Translated by James Hunter. Darlow & Moule Mode of access: Internet. Full sheep (rubbed, spine back partly detached): label of Watkins, binder. Inscription of Mrs. Cathrine McCorrister with her signature and note: present from Rev. A.D. Hunter; signature of J.B. Silcox, Pastor, Central Church, Winnipeg, Man.; bookplate and embossed stamp of Library of the Theological Colleges at Divinity Hall, Montreal (donor: the library of the late Rev. J.B. Silcox).